KESALAHAN KALIMAT DALAM TEKS EKSPOSISI SISWA KELAS X SMA ADABIAH PADANG - Kemala, Anisia; Manaf, Ngusman Abdul; Emidar, Emidar (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this research are four, (1) describe the error text of the sentence in the exposition in terms of structure function syntax, (2) describe the error in the text of the sentence in terms of wastage the elements of a sentence, (3) describe the errors the sentence in the text of the exposition in terms of word choice, and (4) describe the error text of the sentence in the exposition in terms of spelling grade X SMA Adabiah Padang. This type of research is a qualitative descriptive method. Research data is the wrong phrase in the text of the exposition. Data collection was done through the study of documentation. Based on the findings of the research, the error text sentences in the exposition are in qualified students. Errors found there are four, (1) in terms of the structure of the function syntax in the form of a mandatory element of lack or absence of the item, (2) in terms of wastage elements of a sentence in the form of an overlap the use of predicate, konjungtor, the plural marker, and time, (3) in terms of the choice of words in the form of inaccuracy of the concept, the value of flavor, and the context of use, and (4) in terms of spelling in the form of inaccuracy of the wearing of capital letters, writing words, and punctuation.Kata kunci: kesalahan kalimat, teks eksposisi